La atención temprana en el desarrollo psicomotriz grueso de las niñas/os con Síndrome de Down de 3-5 años de edad, que asisten al (C.A.D.E) de la ciudad de Loja. Período marzo- julio de 2013 - Peñaranda Luzuriaga, Alexandra Elizabeth (2016)
The research was headed for the purpose of conducting a study on "Early Intervention in psychomotor development THICK GIRLS / OS with Down Syndrome ages 3-5, ATTENDING THE (CADE) in the city of Loja. PERIOD MARCH-JULY 2013 ". In order to determine the influence of early intervention in the thick psychomotor development of children with Down syndrome 3-5 years of age, who attend the Rehabilitation Centre "CADE" in the city of Loja. The methodology, which ruled the investigation was based on the methods: scientific, hermeneutical, deductive and inductive, descriptive, analytical and synthetic statistical model, the technique was applied to therapists Survey of Early Warning area around the main areas in which they work, and as an instrument, the Abbreviated Scale of Motor Development of Nelson Ortiz Pinilla, to develop research a population of 6 children was taken with Down syndrome children, aged 3-5 years was used and 7 therapists area early attention. Once collected, organized and analyzed the information it was concluded that the areas of early intervention that most therapists often work with children of 3-5 years with Down syndrome are the motor area and the area of language and based on this research has built a proposal for early intervention, in order to be used by such personnel in the execution of their therapies.